Potential Adsorption of Leonardite for Heavy Metal Ions Removal from Aqueous Solution - Thongkam, Thinikan; Hemavibool, Khuanjit; Klamtet, Jintana; Ouypornkochagorn, Sairoong (Science Essence Journal, 2020)
ABSTRACT The potential of leonardite as an adsorbent for the removal of heavy metal ions, Cu(II) and Mn(II), from aqueous solutions was investigated. The adsorption parameters included pH and contact time were optimized in the batch treatment process. The adsorption kinetics of leonardite for heavy metal ions were followed the pseudo-second-order model. Adsorption process for removal of Cu(II) has fitted to the pseudo-second-order kinetic model, while that of Mn(II) has followed the pseudo-first-order. The adsorption of leonardite for both metals was fitted well with Langmuir and Freundlich isotherms. The maximum adsorption capacity was 41.67 and 11.57 mg g-1 for Cu(II) and Mn(II), respectively. The results indicated that leonardite waste materials could be employed as a promising adsorbent for removal of Cu(II) and Mn(II) ions from the industrial wastewater treatment process.